High survivorship after catch-and-release fishing suggests physiological resilience in the endothermic shortfin mako shark (Isurus oxyrinchus). (30th September 2015) - French, Robert P.; Lyle, Jeremy; Tracey, Sean; Currie, Suzanne; Semmens, Jayson M.
Abstract : We used satellite tags and blood based analyses to examine the impacts of catch and release angling on the shortfin mako shark. We report high survivorship seemingly unaffected by fight time or physiological stress and recommend that circle hooks should be used to reduce physical damage to these sharks. Abstract : The shortfin mako shark ( Isurus oxyrinchus ) is a species commonly targeted by commercial and recreational anglers in many parts of the developed world. In Australia, the species is targeted by recreational anglers only, under the assumption that most of the sharks are released and populations remain minimally impacted. If released sharks do not survive, the current management strategy will need to be revised. Shortfin mako sharks are commonly subjected to lengthy angling events; however, their endothermic physiology may provide an advantage over ectothermic fishes when recovering from exercise. This study assessed the post-release survival of recreationally caught shortfin mako sharks using Survivorship Pop-up Archival Transmitting (sPAT) tags and examined physiological indicators of capture stress from blood samples as well as any injuries that may be caused by hook selection. Survival estimates were based on 30 shortfin mako sharks captured off the south-eastern coast of Australia. Three mortalities were observed over the duration of the study, yielding an overall survival rate of 90%. All mortalities occurred in sharks angled for <30 min. Sharks experienced increasing plasma lactate with longer fight times and higher sea surface temperatures (SSTs), increased plasma glucose at higher SSTs and depressed expression of heat shock protein 70 and β-hydroxybutyrate at higher SSTs. Long fight times did not impact survival. Circle hooks significantly reduced foul hooking when compared with J hooks. Under the conditions of this study, we found that physical injury associated with hook choice is likely to have contributed to an increased likelihood of mortality, whereas the high aerobic scope associated with the species' endothermy probably enabled it to cope with long fight times and the associated physiological responses to capture.